Grouth Respons and Antioxidant Activity of Melinjo While Salt Stress - rio azimah afitollah nur (Universitas Sumatera Utara, 2018)
This experiment aimed to determine the growth response and the protein content of antioxidants in the seeds melinjo age of 3 months after administration of the compound NaCl to salt stress condition. Research using a completely randomized design (CRD) with one factor different concentrations of NaCl, 0 mM NaCl; 25 mM NaCl; 50 mM NaCl; 75 mM NaCl and 100 mM NaCl. The parameters observed plant growth, total soluble protein content, activity of antioxidant proteins and protein banding pattern. The results showed that the growth parameters of seedlings melinjo showed no significant with the provision of NaCl except in wet weight, dry weight and chlorophyll content in total, while the total content of protein and antioxidant activity decreased on treatment of 25 and 50 mM NaCl concentration, then climbed back on treatment 75 and 100 mM, namely the 100 mM obtained total protein content of 3.33 mg / g, 78.7% ABTS reduction activity with IC50 values ​​of 0.8 mg / mL). The pattern of protein bands showed different band patterns in the treatment of 100 NaCl. Keywords: Melinjo, NaCl, Protein, Antioxidant Activity.